Climate change mitigation, adaptation and health related issues: A comparative analysis of Sin Chew Daily and China Press coverage / Cheong Jun Rong - Cheong, Jun Rong (2019)
In this decade alone, climate change is a global problem and it is more likely caused by human activities and human greed. So far, studies on media representations of climate change have less concentration on Asian countries compared to Western societies. Since climate change brings about the negative effects on public health, adaptive strategies are needed to address negative health consequences. The research aims to examine and make a contrast in the portrayal of Malaysia’s Chinese newspaper on climate change mitigation and adaption with health-related issue from January 2015 to December 2016. Climate change is one of the most pressing issues and the media play a key role in shaping public perceptions and policy adaptation. Therefore, the agenda setting theory was used to guide this study. The methodology used in the study is quantitative content analysis. Two major Chinese newspapers in Malaysia which are Sin Chew Daily and China Press were chosen as content analysis materials as both newspapers have the highest readership and circulation compare with others Malaysia Chinese newspaper. A total of 183 news articles has been analyzed from Sin Chew Daily while China Press contributed a total of 103 news on climate change mitigation and adaptation issue. Through the analysis of Malaysia major Chinese newspaper, both newspapers have a different level of media attention on climate change mitigation and adaptation issue. The media attention includes news monthly distribution, news focus, news perception, news genre and domesticity. Both newspapers mentioned above use different ways to report climate change issue. The greater of media attention on climate change issue, the community would be more aware of this issue.